2015
DOI: 10.3390/life5021301
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Code Evolution Reveals the Neutral Emergence of Mutational Robustness, and Information as an Evolutionary Constraint

Abstract: The standard genetic code (SGC) is central to molecular biology and its origin and evolution is a fundamental problem in evolutionary biology, the elucidation of which promises to reveal much about the origins of life. In addition, we propose that study of its origin can also reveal some fundamental and generalizable insights into mechanisms of molecular evolution, utilizing concepts from complexity theory. The first is that beneficial traits may arise by non-adaptive processes, via a process of “neutral emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 205 publications
(168 reference statements)
1
22
0
Order By: Relevance
“…The problem with such work is that substitution matrices such as PAM are employed which leads to a tautology (and the claim of the optimality of the natural code) since these matrices are the result of the natural genetic code (Di Giulio, 2001). For other references on the topic the reader is referred to Massey (2015).…”
Section: Resultsmentioning
confidence: 99%
“…The problem with such work is that substitution matrices such as PAM are employed which leads to a tautology (and the claim of the optimality of the natural code) since these matrices are the result of the natural genetic code (Di Giulio, 2001). For other references on the topic the reader is referred to Massey (2015).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the potential tendencies of this code 435 to minimize the errors may be a by-product of this process [Di Giulio, 2016, Di Giulio, 436 2017. Other studies have also showed that no direct selection for the error minimization 437 was necessary to produce the genetic codes with this property, which could have evolved 438 as a result of gene duplications of adaptors and charging enzymes [Massey, 2015, Massey, 439 2016. Interestingly, the optimization of biological systems to minimize the harmful 440 effects of mutations does not have to require changes in the genetic code because the 441 mutational pressure can be subjected to this optimization around the fixed genetic 442 code [Dudkiewicz et al, 2005, Mackiewicz et al, 2008, B lażej et al, 2015 2017].…”
mentioning
confidence: 99%
“…Hence the error minimization theory of code evolution, under which the structure of the code is determined by selection for robustness to errors. Extensive quantitative analyses that employed cost functions differently derived from physico-chemical properties of amino acids have shown that the code is indeed highly resilient, with the probability to pick an equally robust random code being on the order of 10 -7 -10 -8 [14,15,[61][62][63][64][65][66][67][68]. Obviously, however, among the ~10 84 possible random codes, there is a huge number with a higher degree of error minimization than the SGC.…”
Section: The Three Principal Scenarios Of the Code Origin And Evolutimentioning
confidence: 99%
“…Given the confidently derived consensus set of ancient amino acids and the unavailability of the late amino acids before complex biosynthetic pathways evolved (see discussion of The theme of evolution of error minimization as a neutral consequence, or by-product, of the code expansion has been thoroughly developed in several recent studies [64,67,68].…”
Section: Primordial Expansion Of the Codementioning
confidence: 99%
See 1 more Smart Citation